The impact of near infrared fluorescence imaging on parathyroid function after total thyroidectomy. Issue 5 (29th June 2020) - Kim, Yoo Seok; Erten, Ozgun; Kahramangil, Bora; Aydin, Husnu; Donmez, Mustafa; Berber, Eren
Abstract: Background: Compared with conventional thyroidectomy, hypocalcemia rate was reported to be lower after total thyroidectomy (TT) utilizing near infrared fluorescence imaging (NIFI). The aim of this study is to evaluate the impact of NIFI on postoperative parathyroid function after TT. Methods: This was a retrospective institutional review board‐approved study comparing 100 patients who underwent TT with NIFI guidance and 200 patients without, by the same surgeon. Clinical parameters were compared using χ 2 and t test. Results: Average number of parathyroid glands identified intraoperatively was similar between two groups. However, rate of incidental parathyroidectomy was higher in conventional (14%) versus NIFI group (6%) ( P  = .039), despite similar (4% vs 6%, respectively) autotransplantation rates ( P  = .562). Incidences of transient (6.5% vs 5.0%) and permanent (0.5% vs 0%) hypocalcemia were not statistically different between conventional and NIFI groups ( P  = NS). Conclusion: The use of NIFI during thyroidectomy may decrease the rate of incidental parathyroidectomy by increasing the ability of the surgeon to recognize parathyroid glands with fluorescent contrast distinction. Nevertheless, in contrary to recent reports in literature, postoperative hypocalcemia rate was not altered compared with conventional technique, suggesting that preservation of parathyroid vasculature, rather than an augmented ability to detect the glands, may dominantly affect postoperative function.